2012
DOI: 10.1016/j.jcot.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic osteomyelitis of ilium presenting as an expansile mutiloculated lytic lesion – A case report

Abstract: Chronic iliac osteomyelitis classically presents radiologically as an ill defined radiolucent lesion with moth eaten appearance along with periosteal reaction and sequestrum formation. Our case report presents a rare radiological picture of iliac bone osteomyelitis in the form of an expansile mutiloculated lytic lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Infection is commonly polymicrobial. Staphylococcus aureus is the most commonly observed organism, as also seen in our case [2].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Infection is commonly polymicrobial. Staphylococcus aureus is the most commonly observed organism, as also seen in our case [2].…”
Section: Discussionsupporting
confidence: 78%
“…Staphylococcus aureus is the most commonly identified organism in these infections. Osteomyelitis of the pelvis is uncommon, constituting 2-11% of all osteomyelitis cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ando et al reported 3 cases of eosinophilic granuloma of the pelvis in children, and each presented different radiological features and clinical courses [ 4 ]. Another case was reported as a diagnostic dilemma, and one of the few documented cases of osteomyelitis presented a nonspecific radiological picture [ 5 ]. Because the imaging features vary widely and radiological images differ among cases of iliac bone destruction in children, it is difficult to obtain a correct diagnosis when relying only on clinical and imaging features [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%